Improving primary health care to increase efficiency - Kornatsky, V. M.; Mikhal’chuk, V. N.; Diachenko, L. O. (Journal of Education, Health and Sport, 2017)
Thus, the convergence of medicine, psychiatry and psychology is the reality of today to eliminate the imbalance, psychosomatic health. The role of medical practice in the correction of psychosomatic disorders is large, but insufficient. Complementary medical becomes a psychological resource in decision psychosomatic problems. A study of the leading role of psychogenic factors and mechanisms of somatic response to stressful situations, underlying the formation of the most common and socially significant diseases, is a current trend psychosomatic direction in the PC. The data obtained may become the basis for developing measures for the identification, treatment, and prevention of psychosomatic disorders in conditions of emotional stress and their prevention. Successful interdisciplinary interaction fosters the following principles: collegiality in matters of surveillance, social functioning capabilities; continuity in matters of treatment and preventive care; adherence to the principles of medical ethics and deontology; implementation of accounting volume of medical care. The formation of a new system will bring to the population high-tech methods of diagnostics and treatment, strengthen the development of the system of prevention of socially significant diseases and expand the possibilities of rehabilitation.